2017
DOI: 10.3892/ol.2017.5603
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin 1 promotes the proliferation and malignant transformation of pancreatic intraductal papillary mucinous neoplasms

Abstract: Abstract. Pancreatic intraductal papillary mucinous neoplasms (IPMNs) are a type of pancreatic tumor, which have been identified following improvements in diagnostic imaging. However, the malignant transformation of IPMN has been difficult to diagnose clinically. To date, the mechanisms driving the progression of IPMN to cancer remain to be fully elucidated. The present study focused on Stathmin 1 (STMN1), a protein that is associated with the development of various types of cancer. The expression of STMN1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…STMN1 was found to be abnormally expressed in tumors, resulting in the malignant phenotypes of several malignancies, including lung squamous cell carcinoma 14 , pancreatic- 16 , liver- 27 , and breast-cancer 15 . Therefore, STMN1 inhibition could be crucial target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STMN1 was found to be abnormally expressed in tumors, resulting in the malignant phenotypes of several malignancies, including lung squamous cell carcinoma 14 , pancreatic- 16 , liver- 27 , and breast-cancer 15 . Therefore, STMN1 inhibition could be crucial target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It encodes a ubiquitous cytosolic phosphoprotein belonging to the stathmin family of genes and plays an essential role in the cellular environment aimed at an intracellular relay for integrating regulatory signals. Numerous researchers have confirmed that the dysregulation of the STMN1 gene contributed to tumor progression in lung squamous cell carcinoma 14 , breast cancer 15 , and pancreatic cancer 16 . STMN1 has been found to be elevated in HCC, which has been linked to the occurrence and advancement of cancer 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…All the samples were scored as 0, 1, 2, 3, 4, 6, or 9. Samples with scores of 0-4 were considered low expression, and samples with scores of 6-9 were considered high expression [ 21 ]. Evaluation of the stained sections was performed by two pathologists.…”
Section: Methodsmentioning
confidence: 99%